Maintaining Query Performance through Table Rebuilding & Archiving - Andriyani, Widyastuti; Pujianto, Pujianto (IJCCS (Indonesian Journal of Computing and Cybernetics Systems), 2024)
Despite the system previously utilizing optimal query configurations and database settings, the transaction table in the database, which is undergoing significant numerical increases and notable queries and updates on each line, has seen a drop in query speeds simultaneous with data growth. This situation arises due to an increase in disk space in the database tablespace, which results from block fragmentation. At times, database engines do not detect this problem, thereby overlooking it in the database recommendation engine. Lacking an understanding of the fundamental issue, database engineers need analysis and strategies to maintain the query speed of the transaction table in the relational database